Bone marrow mesenchymal stem cells-derived exosomal miR-185-5p plays a protective role in high-glucose stimulated human retinal microvascular endothelial cells in vitro by regulating CXCL8: BM-MSCs-derived miR-185-5p on angiogenesis in DR - Zhou, Lin; Wang, Weixia (Cellular and Molecular Biology, 2023)
In this study, we intended to probe the impacts and mechanism of bone marrow mesenchymal stem cells (BM-MSCs)-derived exosomal miR-185-5p on angiogenesis and inflammatory response in diabetic retinopathy (DR). Based on the GEO database, we found that CXCL8 was differentially expressed in DR, and GO and KEGG analysis further revealed that CXCL8 was associated with angiogenesis and inflammatory response. Upstream miR-185-5p of CXCL8 was predicted by bioinformatics analyses and the binding relation between miR-185-5p and CXCL8 was further validated by dual-luciferase reporter assay. Human retinal microvascular endothelial cells (HRMECs) were added with high-glucose (HG) to construct a DR cell model. Exosomes secreted by BM-MSCs were isolated, and the DR cell model was treated with different intervention vectors of exosomes. Cell proliferation and angiogenesis were measured by MTT assay and Matrigel angiogenesis experiment, respectively, and the levels of VEGF, TNF-α, IL-1β as well as IL-6 were examined by ELISA. The results showed that CXCL8 was highly expressed in HRMECs treated with HG. CXCL8 knockdown inhibited the proliferation, angiogenesis as well as concentration of inflammatory factors in DR cell models, while overexpression of CXCL8 had the opposite effects. CXCL8 was verified to be directly targeted by miR-185-5p. BM-MSCs-derived exosomes inhibited the proliferation, angiogenesis and concentration of inflammatory factors of DR cell models, but this effect was partly reversed by miR-185-5p inhibitor. In conclusion, BM-MSCs-derived exosomal miR-185-5p inhibits angiogenesis and inflammatory response in DR cell models via regulating CXCL8. BM-MSCs-derived exosomal miR-185-5p is expected to be the therapeutic target of DR.